Reforming the prerogative - Hazell, Robert; Foot, Tim (London [England] : Hart Publishing, 2022)
"The concept of the prerogative is still a source of mystery to most observers; this book demystifies it. It clarifies the respective roles of government, Parliament and the courts, in defining the extent of prerogative powers, and regulating their use in specific cases, and looks at the powers which should be codified in statute and which should be regulated by convention, and which could be left at large. The book considers the role of Parliament; and if Parliament is to have a stronger role, what additional powers or resources it might need to exercise that role responsibly. In their 2019 election manifesto, the Conservative party stated that 'After Brexit we also need to look at the broader aspects of our constitution, the relationship between the Government, Parliament and the courts; the functioning of the Royal Prerogative; ...' The prerogative has traditionally remained in the shadows, but the fevered parliamentary debates over Brexit thrust it centre stage. The controversies ranged from the role of parliament in assenting to treaties, to the prorogation and dissolution of parliament, to the grant or withholding of Royal Assent. This book provides a clear and full analysis of the function of the royal prerogative in the changing landscape of the British constitution."--
Part 1: Introduction -- 1. Introduction -- 2. Historical Background -- 3. Recent Developments -- Part 2: The Personal Prerogatives of the Monarch -- 4. Appointing and Dismissing Ministers -- 5. Summoning, Dissolving and Proroguing Parliament -- 6. Royal Assent, and Executive Veto of Legislation -- Part 3: Prerogative Powers Exercised by the Executive -- 7. The War Making Power -- 8. Making and Ratifying Treaties -- 9. Regulating the Civil Service -- 10. Public Appointments -- 11. Prerogative of Mercy -- 12. Issue of Passports -- 13. The Grant of Honours -- 14. Public Inquiries -- Part 4: The Prerogative in Comparative Context -- 15. Reform of the Prerogative in Australia, Canada and New Zealand -- 16. Reserve Powers in Other Countries with Written Constitutions -- Part 5: Reform of the Prerogative -- 17. The Role of the Courts -- 18. The Role of Parliament -- 19. Strengthening and Codifying Conventions -- 20. Conclusions -- Appendices -- Bibliography
Includes bibliographical references.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Prerogative, Royal -- Great Britain; Constitutional law -- Great Britain; Great Britain -- Politics and government -- 21st century; Electronic books